2020
DOI: 10.1002/ppp.2038
|View full text |Cite
|
Sign up to set email alerts
|

Identifying historical and future potential lake drainage events on the western Arctic coastal plain of Alaska

Abstract: Arctic lakes located in permafrost regions are susceptible to catastrophic drainage. In this study, we reconstructed historical lake drainage events on the western Arctic Coastal Plain of Alaska between 1955 and 2017 using USGS topographic maps, historical aerial photography (1955), and Landsat Imagery (ca. 1975, ca. 2000, and annually since 2000). We identified 98 lakes larger than 10 ha that partially (>25% of area) or completely drained during the 62‐year period. Decadal‐scale lake drainage rates progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 39 publications
0
59
1
Order By: Relevance
“…Using the developed lake origin product and decadal patterns of lake drainage in northern Alaska, we find the most vulnerable periglacial lakes to drain between 1985-1989 and 2015-2019 were small Thermokarst (non-yedoma) and large Yedoma lakes, respectively, whereas the most resilient lakes were large and medium-sized glacial and large Maar lakes ( Table 2). The discrepancy between lake drainage is likely due to the associated differences in permafrost ice content [14,17], as low to moderate ice content found adjacent to glacial and Maar lakes makes them relatively insensitive to thermo-erosional gully formation that is often responsible for abrupt lake drainage [18,35]. Although we did not observe any drainage of Maar lakes during our~30 year observation period (likely associated with low sample size and geologic origin), they are not entirely resistant to drainage.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Using the developed lake origin product and decadal patterns of lake drainage in northern Alaska, we find the most vulnerable periglacial lakes to drain between 1985-1989 and 2015-2019 were small Thermokarst (non-yedoma) and large Yedoma lakes, respectively, whereas the most resilient lakes were large and medium-sized glacial and large Maar lakes ( Table 2). The discrepancy between lake drainage is likely due to the associated differences in permafrost ice content [14,17], as low to moderate ice content found adjacent to glacial and Maar lakes makes them relatively insensitive to thermo-erosional gully formation that is often responsible for abrupt lake drainage [18,35]. Although we did not observe any drainage of Maar lakes during our~30 year observation period (likely associated with low sample size and geologic origin), they are not entirely resistant to drainage.…”
Section: Discussionmentioning
confidence: 67%
“…Numerous studies have identified heterogeneous spatial and temporal patterns of lake drainage across northern Alaska [6,17,18,34,35,37,[45][46][47]. In addition to landscape history, interacting climate and environmental controls are likely responsible for elevated rates of lake drainage, as anomalous precipitation, temperature, and snow cover may influence patterns of lake change [17,18,37,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An annual temporal resolution of time series analysis allows to assess highly dynamic permafrost pulse disturbances and possibly even identify the main disturbance drivers. Thermokarst lake dynamics and particularly lake drainage events have currently only been identified and described based on multiple-date images or trend analysis [93][94][95][96]. An annual time series analysis will help to narrow down change drivers and identify inter-annual lake dynamics, such as partial or full drainage, or intermittent infilling, which otherwise remain undiscovered in multi-year trend data.…”
Section: Discussionmentioning
confidence: 99%